Assessing the Relevance of Undergraduate Auditing Education: A Scoping Review - Diana Tien Irafahmi (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2019)
The objective of this scoping review is to map the existing literature that asses the relevance of undergraduate auditing education to meet contemporary audit practice. The scoping review followed the protocol outlined by Arksey and O'Malley (2005) that has five main stages: (1) identifying the research questions; (2) identifying relevant studies; (3) study selection; (4) charting the data, and (5) collating, summarizing and reporting the results. The studies reviewed were selected from three electronic databases: Proquest, Taylor & Francis, and Science Direct within 25 years time span (1995-2019). The results of the scoping review indicated that the majority of the studies recognize a shift both in terms of content and pedagogy to keep its relevance to professional demand. The shift needs to more emphasize on content as a gap still exists between auditing educators and practitioners.